A Critical Review of A Buenos Aires Collection (Rugs and Art Tribal Bird Rugs and Others) - Azadeh Pashootanizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Arab Jinni’s carpet is an example of Suleimani’s carpets. This carpet has primitive images and symbolic motifs. This sample of Suleiman carpets has different characteristics than visual/pictorial carpets. This kind of carpet has a unique form and color combinations that represent the metaphysical world. A non-Iranian man writes part of his book to the Arab Jinni’s carpet. The name of his book is A Buenos Aires Collection: Rugs and Art/Tribal Bird Rugs and Others. It is very important to publish an image of this kind of rare carpet that is not currently in Iran and is not even woven in Fars province. The home country of Arab Jinni’s carpet weavers is Fars province. The research method in this paper is content and descriptive analysis. The knitters of this carpet are migrants of Fars province, and their designs reflect their tribal culture. In different literary and folklore texts of Iran, Fars province is called the land of Prophet Solomon. The stories of Prophet Solomon are related to the religious and geographical beliefs associated with the goddess Nahid and Prophet Khidr. The Prophet Khidr and the Nahid goddess have shared duties, and this has led to their similarity and consistency. Carpets with mental and improvised maps woven in the tribes depict the indigenous and religious beliefs of the people.